Tourism Nation vs. Cultural Confidence: A Comparative Analysis of Japan’s and China’s Strategies for Global Image Building - Huang, Yaojie (Journal of Cultural Analysis and Social Change, 2025)
This study investigates how Japan’s Tourism Nation strategy and China’s Cultural Confidence-based tourism development function as distinct models of national image building in the post-pandemic era. Background: Both nations increasingly employ tourism as a tool for soft-power projection and economic revitalization. Gap: Existing research often analyzes their tourism or cultural policies separately, lacking a comparative understanding of how policy instruments, objectives, and image narratives differ across governance systems. Method: Using a qualitative, multi-case comparative approach that integrates document analysis, discourse interpretation, and policy comparison, the study applies a tri-layered analytical model encompassing policy design, narrative construction, and international perception. Results: Findings reveal that Japan’s market-oriented and decentralized Tourism Nation emphasizes experiential authenticity, openness, and regional revitalization, while China’s centralized, ideology-driven Cultural Confidence framework prioritizes cultural heritage, moral legitimacy, and civilizational continuity. Both achieve soft-power gains through divergent pathways, Japan through experiential trust, China through symbolic authority. Impact: The research advances theoretical understanding of tourism as a governance-based communication mechanism and offers practical insights for policymakers seeking to align economic performance with cultural authenticity in global image strategies.